Imprensa operária e educação: debates e demandas educacionais dos trabalhadores de Belo Horizonte (1987-1930) - Renata Garcia Campos Duarte (2019)
This thesis aims to identify and discuss the educational demands of workers from Belo Horizonte, based on the analysis of newspapers and magazines of four workers associations: Associação Beneficente Tipográfica, Centro Confederativo dos Operários, Confederação Auxiliadora dos Operários, and Confederação Católica do Trabalho, between the last decade of the 19thcentury and the end of the 1920s. The hypothesis is that educational public policies, through state and municipal reforms, did not contemplate the needs of workers and their children and were not effectively applied. Thus, there were initiatives promoted by workers associations, published in their newspapers and magazines, which aimed to promote workers education. To develop the research, besides the bibliographic survey, we analyzed the following newspapers and documents from those associations: O Labor (1905-1906), from Confederação Auxiliadora dos Operários, O Confederal (1907), from Centro Confederativo dos Operários, O Operário (1920-1929), from Confederação Católica do Trabalhoand the magazine of Associação Beneficente Tipográfica(1906, 1908, 1911, 1920, 1925, 1930, 1936). Besides these sources we researched other ones: statutes of workers associations, official documents, laws from the state of Minas Gerais, especially those related to the implementation ofbasic school, reforms on public education, and adult education, as well as yearbooks and censuses. To analyze the documents, we used conceptual theoretical studies on social history, focusing on the contributions of E. P. Thompson, and others on history of work, history of Belo Horizonte, and history of education. The thesis is divided into four chapters. The first presents the bibliographical review of studies on worker and workers movement in Brazil, focusing on the particularities of Belo Horizonte. The second chapter deals with the appearance of the four analyzed workers association, their dynamic of construction and development in Belo Horizonte, the new capital of Minas Gerais, and their relations in the processes of debate, elaboration, and implementation of governmental educational policies. The third chapter approaches the objectives and materiality of the newspapers and magazines of the workers associations to understand the educational demands they proposed. Finally, the fourth chapter relates and analyzes such demands comparing them with the educational reforms established in the period of implementation of public basic school and adult education.